EFFECT OF MAGNETIC AND QUALITY OF IRRIGATION WATER IN MEAN WEIGHT DIAMETER AND AGGREGATION INDEX FOR CLAY LOAM SOIL DURING GROWTH STAGES OF BARLEY CROP - K. A. AL-Mosawi; S. S. Al-Hadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Field experiments were conducted at the Research Station College of Agriculture, University of Basra at Garmat Ali district. The experiments were carried out during the winter season 2012-2013 in clay loam soil. The purpose of the research was to study the effect of water magnetizing and the quality of irrigation water in mean weight diameter and aggregation index during the plant growth stages (the beginning of the forest and the beginning of flowering and after harvesting) for barley crop (Hordium vulgare L.). The magnetizing of irrigation water treatments Included, non-magnetized water (M0) and water magnetized (M1). The irrigation water quality treatment included five types of water namely, tap water (TW), River water (RW), wastewater (WW),treated sewage water passed through sand filter (WWT) and mixed water (MW) ( 50% RW + 50% WWT).The experiments were conducted using factorial experiments according to randomized complete block design (RCBD). The irrigation water was added on the basis of the shortfall in the level of water of the evaporation pan installed in the field. The amount of water added was 100% of the amount vaporized water plus 20% as leaching requirements. The results showed that: Magnetization of irrigation water resulted in a significant increase in the mean weight diameter and aggregation index for both layers 0-30cm and 30-60 cm compared with non-magnetized water. The order of the effect of treatments on the mean weight diameter and aggregation index is WW >TW >WWT >MW >RW for both layers. The results showed that the values of both parameters increased as growth season progress and layer 0-30 cm surpassed layer of 30-60 cm.